Challenges of Collective Development through Islamic Endowments – Case of LAKIM in Malaysia - Siti Normala Sheikh Obid; Rashedul Hasan, (Journal of Human Development and Communication (JoHDeC), 2025)
Waqf is a charitable vehicle in Islam with the ability to contribute toward deep socio-economic development. This paper focuses on the ability of a Public Trust Foundation toward collective development through a fund disbursement system similar to Waqf. The study utilises secondary data gathered through document analysis to portray various contributions made by LAKIM in educational development and challenges faced by the institutions along the way. Efficiency and Agency theory are used as a basis to explain the performance of LAKIM in managing Waqf fund and develop a conceptual framework for collective development. This study addressed several legal, administrative, accounting and management issues that are affecting Waqf’s ability toward contributing toward educational development in Malaysia. Differences between western institutions and LAKIM are drawn with clear examples, and evidence of efficient performance in managing Waqf fund are highlighted through the study. Primary data through survey and interviews could not be provided due to the conceptual nature of the paper. Issues addressed by the paper will allow stakeholders to understand the true potential of Waqf in making sustainable development by contributing to the educational sector. Studies on Waqf in Malaysia have previously focused on the State Islamic Religious Councils (SIRCs) while this study is the first to introduce LAKIM, a private Trust that contributes toward educational and social development.